Evaluación del componente nutricional del Programa Buen Comienzo de Medellín (2016)
ABSTRACT: Nutrition programs in Colombia have evolved in parallel with the prevailing economic and political models in every age. At the same time, the methods to program evaluation have changed over time, resulting in quantitative, qualitative or mixed approaches. The city of Medellin in 2004 implemented the social Program “Buen Comienzo” in order to provide comprehensive care to children from gestation to age five. Objective: Carried out an assessment to evaluate the structure, process and results of the children Program “Buen Comienzo” of the municipal government in Medellin. Materials and Methods: This study conducted an evaluation of the nutritional component of the social Program Buen Comienzo using a mixed evaluation method by combining three dimensions: structure, process and outcomes with triangulation methods. Results: The results show the relevance of the food supply for all actors, the changing eating habits produced by the program not only on children but also their families and the impact on the nutritional status of children attending the program; results also point out the need of the program to provide better tools to educators to develop daily activities. Conclusions: The evaluation showed that children who attend the program positively change their dietary habits, acquire skills and routines that promote their health and nutritional status, extending those changes to families.